Growth inhibitory effect and Chk1-dependent signaling involved in G2/M arrest on human gastric cancer cells induced by diallyl disulfide - H. Ling (Brazilian Journal of Medical and Biological Research, 2010)
Diallyl disulfide (DADS) inhibits growth and induces cell cycle G2/M arrest in human gastric cancer MGC803 cells. In this study, 15 mg/L DADS exerted similar effects on growth and cell cycle arrest in human gastric cancer BGC823 cells. Due to the importance of cell cycle redistribution in DADS-mediated anti-carcinogenic effects, we investigated the role of checkpoint kinases (Chk1 and Chk2) during DADS-induced cell cycle arrest. We hypothesized that DADS could mediate G2/M phase arrest through either Chk1 or Chk2 signal transduction pathways. We demonstrated that DADS induced the accumulation of phosphorylated Chk1, but not of Chk2, and that DADS down-regulated Cdc25C and cyclin B1. The expression of mRNA and total protein for Chkl and Chk2 was unchanged. Chk1 is specifically phosphorylated by ATR (ATM-RAD3-related gene). Western blot analysis showed that phospho-ATR was activated by DADS. Taken together, these data suggest that cell cycle G2/M arrest, which was associated with accumulation of the phosphorylated forms of Chk1, but not of Chk2, was involved in the growth inhibition induced by DADS in the human gastric cancer cell line BGC823. Furthermore, the DADS-induced G2/M checkpoint response is mediated by Chk1 signaling through ATR/Chk1/Cdc25C/cyclin B1, and is independent of Chk2.